Survival analysis of recurrent ovarian cancer under different PARP inhibitor treatment patterns: a single-center retrospective study - Shen, Jingtian; Wang, Xi; Mpano, Olivier; Wang, Ying; Shan, Yihan; Lou, Xinning; Ye, Piaopiao; Yan, Xiaojian (Frontiers in Oncology, 2025)
ObjectiveTo compare the effects of different treatment modes containing PARPis and traditional treatment modes on the survival of patients with recurrent ovarian cancer.MethodsFrom December 2012 to December 2023, 131 recurrent ovarian cancer patients were screened. The patients were followed up retrospectively, and the relevant data was collected and analyzed.ResultsEighty-three patients used PARPis throughout the treatment process, and the median OS was not reached. Forty-eight patients did not use PARPis, and the median OS was 45.4 months. The two groups ‘ BRCA gene status, NACT, postoperative residual disease status, and PFI differ (P < 0.05). There was no significant difference in recurrence characteristics between the PARPis use and non-use groups in first-line maintenance therapy (P < 0.05). The use of PARPis, CA125 level and PFI were the independent influencing factors of OS in patients with recurrent ovarian cancer (P < 0.05). The median OS of patients with PARPis maintenance treatment in the single-line, second-line and last-line has not been reached. The median OS in the multi-line group was 69.5 months.ConclusionThe use of PARPis, CA125 level and PFI were independent influencing factors of OS in patients with recurrent ovarian cancer. The first-line maintenance use of PARPis will not cause differences in disease recurrence characteristics. Compared with the patients without PARPis, patients with recurrent ovarian cancer receiving PARPis maintenance therapy have longer OS. The group of patients with PARPis maintenance treatment in the second and last lines showed better OS (P < 0.05). However, OS was not significantly different between the second-line and last-line groups (P < 0.05). There was no significant difference in OS between the multiple-line use PARPis and single-line use PARPis groups.